Pengaruh Metode Pembayaran Cash on Delivery dan Online Customer Review Terhadap Keputusan Pembelian Pada Tiktok Shop di Kota Depok - Angelly Andriani; Joni Haryanto (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This research aims to determine the effect of cash on delivery and online customer reviews on purchasing decisions at Tiktok Shops in Depok City. The type of research used is quantitative research. The sampling technique is non-probability sampling, namely the purposive sampling method using 130 respondents who have made purchases at the Tiktok Shop. The data collection technique used a questionnaire on the Google form with a Likert scale of 1-5 with 26 statements. The data analysis technique uses multiple linear regression with the help of SPSS 25. The results of this study indicate that the cash on delivery variable X1) has a positive and significant influence on purchasing decisions (Y). Online customer reviews (X2) have a positive and significant influence on purchasing decisions (Y). Cash on delivery (X1) and online customer reviews (X2) have a simultaneous positive influence on purchasing decisions (Y) at the Tiktok Shop in Depok City.